Conductive polymer-containing liquid, conductive laminate having a cured layer of the conductive polymer-containing liquid, and method for producing the same
Patent Information
- Application Number
- JP2021138613
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-08-27
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-08-27
AI Technical Summary
【0007】 本発明の導電性高分子含有液は、分散安定性に優れる。換言すれば保存安定性に優れる。 本発明の導電性積層体は導電性が良好な導電層を備える。 本発明に関する導電性積層体の製造方法によれば、使用する導電性高分子含有液の分散安定性が優れ、基材に対する濡れ性も優れるので、導電性積層体を容易に製造できる。
Smart Images

Figure 0007621223000001 
Figure 0007621223000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive polymer-containing liquid that contains a π-conjugated conductive polymer, and a conductive laminate having a cured layer of the conductive polymer-containing liquid, and a method for producing the same. [Background technology]
[0002] A conductive polymer dispersion containing a conductive complex in which a π-conjugated conductive polymer is doped with a polyanion may be used as a paint or a component thereof for forming a conductive layer. For example, poly(3,4-ethylenedioxythiophene), a π-conjugated conductive polymer, is difficult to disperse in water, but by doping it with polystyrene sulfonic acid to form PEDOT-PSS, its dispersibility in water is improved. When forming a conductive layer by applying a conductive polymer dispersion to a plastic substrate, the conductive polymer dispersion is required to have high wettability with respect to the substrate. For this purpose, a technique has been disclosed in which a conductive complex is reacted with an amine compound to make it hydrophobic, in order to disperse the conductive complex in an organic solvent such as alcohol instead of an aqueous dispersion medium (for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2021-095459 Summary of the Invention [Problem to be solved by the invention]
[0004] However, the method disclosed in Patent Document 1 is restricted in that a hydroxypyridine compound must be used as an essential component in addition to the amine compound bound to the conductive composite.
[0005] The present invention provides a conductive polymer-containing liquid containing a conductive complex that has excellent dispersion stability in isopropyl alcohol without using a hydroxypyridine compound, as well as a conductive laminate having a cured layer of the conductive polymer-containing liquid and a method for producing the same. [Means for solving the problem]
[0006] [1] A conductive polymer-containing liquid containing a conductive complex including a π-conjugated conductive polymer and a polyanion, and isopropyl alcohol, wherein the polyanion is modified by a reaction between a portion of an anionic group of the polyanion and a quaternary ammonium compound, and the content of the isopropyl alcohol relative to the total mass of the conductive polymer-containing liquid is 84 mass% or more. [2] The conductive polymer-containing liquid according to [1], wherein the quaternary ammonium compound includes a water-insoluble quaternary ammonium compound. [3] The conductive polymer-containing liquid according to [1] or [2], wherein the quaternary ammonium compound contains a tetraalkylammonium halide. [4] The conductive polymer-containing liquid according to [3], wherein the tetraalkylammonium halide includes at least one of tetrabutylammonium halide and tetraoctylammonium halide. [5] The conductive polymer-containing liquid according to any one of [1] to [4], further comprising a highly-conductive agent. [6] The conductive polymer-containing liquid according to [5], wherein the conductive agent contains a compound having one or more unsaturated bonds or one or more hydroxyl groups and having 3 to 5 carbon atoms. [7] The conductive polymer-containing liquid according to [5], wherein the conductive agent contains at least one selected from the group consisting of propylene glycol, dimethyl sulfoxide, hydroxyethyl acrylamide, N,N-dimethyl acrylamide, 2,3-butenediol, and 2,3-butynediol. [8] The conductive polymer-containing liquid according to any one of [1] to [7], wherein the π-conjugated conductive polymer contains poly(3,4-ethylenedioxythiophene) or the polyanion contains polystyrenesulfonic acid. [9] A conductive laminate comprising a substrate and a conductive layer formed on at least a portion of the substrate, the conductive layer being made of a cured product of the conductive polymer-containing liquid according to any one of [1] to [8].
[10] A method for producing a conductive laminate, comprising applying the conductive polymer-containing liquid according to any one of [1] to [8] to at least a part of a substrate. Effect of the Invention
[0007] The conductive polymer-containing liquid of the present invention has excellent dispersion stability, in other words, excellent storage stability. The conductive laminate of the present invention comprises a conductive layer having good conductivity. According to the method for producing a conductive laminate of the present invention, the conductive polymer-containing liquid used has excellent dispersion stability and excellent wettability to the substrate, so that the conductive laminate can be easily produced.
[0008] This invention is believed to contribute to SDGs Goal 12, "Responsible Consumption and Production." DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] In this specification and claims, the lower limit and upper limit of a numerical range indicated with "to" are included in the numerical range.
[0010] ≪Conductive polymer-containing liquid≫ A first aspect of the present invention is a conductive polymer-containing liquid that contains a conductive complex that includes a π-conjugated conductive polymer and a polyanion, and isopropyl alcohol (isopropanol). The polyanion is modified by a reaction between a portion of an anion group of the polyanion and a quaternary ammonium compound, and the content of the isopropyl alcohol relative to the total mass of the conductive polymer-containing liquid is 84 mass% or more. In the conductive polymer-containing liquid of this embodiment, the conductive complex may be in a dispersed state or a dissolved state. In this specification, unless otherwise specified, the dispersed state and the dissolved state are not distinguished, and may simply be referred to as the dispersed state.
[0011] [Conductive composite] The conductive complex contained in the conductive polymer-containing liquid of this embodiment contains a π-conjugated conductive polymer and a polyanion. The polyanion in the conductive complex is doped into the π-conjugated conductive polymer to form a conductive complex having electrical conductivity. In the polyanion, only a part of the anionic groups is doped into the π-conjugated conductive polymer, and there are excess anionic groups that are not involved in the doping. Since the excess anionic groups are hydrophilic groups, the conductive composite in which the excess anionic groups are not modified has water dispersibility.
[0012] (π-conjugated conductive polymer) The π-conjugated conductive polymer may be an organic polymer whose main chain is composed of a π-conjugated system, and examples thereof include polypyrrole-based conductive polymers, polythiophene-based conductive polymers, polyacetylene-based conductive polymers, polyphenylene-based conductive polymers, polyphenylenevinylene-based conductive polymers, polyaniline-based conductive polymers, polyacene-based conductive polymers, polythiophenevinylene-based conductive polymers, and copolymers thereof. From the viewpoint of stability in air, polypyrrole-based conductive polymers, polythiophenes, and polyaniline-based conductive polymers are preferred, and from the viewpoint of transparency, polythiophene-based conductive polymers are more preferred.
[0013] Polythiophene-based conductive polymers include polythiophene, poly(3-methylthiophene), poly(3-ethylthiophene), poly(3-propylthiophene), poly(3-butylthiophene), poly(3-hexylthiophene), poly(3-heptylthiophene), poly(3-octylthiophene), poly(3-decylthiophene), poly(3-dodecylthiophene), poly(3-octadecylthiophene), poly(3-bromothiophene), poly(3-chlorothiophene), and poly(3-iodothiophene). thiophene), poly(3-cyanothiophene), poly(3-phenylthiophene), poly(3,4-dimethylthiophene), poly(3,4-dibutylthiophene), poly(3-hydroxythiophene), poly(3-methoxythiophene), poly(3-ethoxythiophene), poly(3-butoxythiophene), poly(3-hexyloxythiophene), poly(3-heptyloxythiophene), poly(3-octyloxythiophene), poly(3-decyloxythiophene), poly(3-dodecyloxythiophene), oxythiophene), poly(3-octadecyloxythiophene), poly(3,4-dihydroxythiophene), poly(3,4-dimethoxythiophene), poly(3,4-diethoxythiophene), poly(3,4-dipropoxythiophene), poly(3,4-dibutoxythiophene), poly(3,4-dihexyloxythiophene), poly(3,4-diheptyloxythiophene), poly(3,4-dioctyloxythiophene), poly(3,4-didecyloxythiophene), poly(3,4-di dodecyloxythiophene), poly(3,4-ethylenedioxythiophene), poly(3,4-propylenedioxythiophene), poly(3,4-butylenedioxythiophene), poly(3-methyl-4-methoxythiophene), poly(3-methyl-4-ethoxythiophene), poly(3-carboxythiophene), poly(3-methyl-4-carboxythiophene), poly(3-methyl-4-carboxyethylthiophene), and poly(3-methyl-4-carboxybutylthiophene). Examples of polypyrrole-based conductive polymers include polypyrrole, poly(N-methylpyrrole), poly(3-methylpyrrole), poly(3-ethylpyrrole), poly(3-n-propylpyrrole), poly(3-butylpyrrole), poly(3-octylpyrrole), poly(3-decylpyrrole), poly(3-dodecylpyrrole), poly(3,4-dimethylpyrrole), poly(3,4-dibutylpyrrole), poly(3-carboxypyrrole), poly(3-methyl-4-carboxypyrrole), poly(3-methyl-4-carboxyethylpyrrole), poly(3-methyl-4-carboxybutylpyrrole), poly(3-hydroxypyrrole), poly(3-methoxypyrrole), poly(3-ethoxypyrrole), poly(3-butoxypyrrole), poly(3-hexyloxypyrrole), and poly(3-methyl-4-hexyloxypyrrole). Examples of polyaniline-based conductive polymers include polyaniline, poly(2-methylaniline), poly(3-isobutylaniline), poly(2-anilinesulfonic acid), and poly(3-anilinesulfonic acid). Among these π-conjugated conductive polymers, poly(3,4-ethylenedioxythiophene) is particularly preferable because of its excellent conductivity, transparency, and heat resistance. The conductive composite may contain one type of π-conjugated conductive polymer, or two or more types of polymers.
[0014] (Polyanion) A polyanion is a polymer having two or more monomer units each having an anionic group in the molecule. The anionic group of the polyanion functions as a dopant for a π-conjugated conductive polymer, improving the conductivity of the π-conjugated conductive polymer. The anion group of the polyanion is preferably a sulfo group or a carboxy group. Specific examples of such polyanions include polymers having a sulfo group, such as polystyrene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyacrylic acid esters having a sulfo group, polymethacrylic acid esters having a sulfo group (for example, poly(4-sulfobutyl methacrylate, polysulfoethyl methacrylate, polymethacryloyloxybenzenesulfonic acid), poly(2-acrylamido-2-methylpropanesulfonic acid), and polyisoprene sulfonic acid; and polymers having a carboxy group, such as polyvinyl carboxylic acid, polystyrene carboxylic acid, polyallyl carboxylic acid, polyacrylic acid, polymethacrylic acid, poly(2-acrylamido-2-methylpropanecarboxylic acid), and polyisoprene carboxylic acid. The polyanion may be a homopolymer in which a single monomer is polymerized, or a copolymer in which two or more monomers are polymerized. Among these polyanions, polymers having a sulfo group are preferred, and polystyrene sulfonic acid is more preferred, since they can provide higher electrical conductivity. The polyanions may be used alone or in combination of two or more kinds. The mass average molecular weight of the polyanion is preferably from 20,000 to 1,000,000, and more preferably from 100,000 to 500,000. The mass average molecular weight is the average molecular weight based on mass measured by gel filtration chromatography and calculated in terms of pullulan.
[0015] When the number of all anionic groups in the polyanion is taken as 100 mol %, the excess anionic groups are preferably from 30 mol % to 90 mol %, more preferably from 45 mol % to 75 mol %.
[0016] The polyanion of the present invention is modified by reacting the excess anion groups (hereinafter also referred to as "part of the anion groups") of the polyanion that are not involved in the dope with a quaternary ammonium compound. That is, the polyanion of the present invention has a substituent (C) formed by reacting the quaternary ammonium compound with the part of the anion groups.
[0017] (Substituent C) The substituent (C) is presumed to be a group represented by the following formula (C).
[0018] -N + R 11 R 12 R 13 R 14 (C) [In formula (C), R 11 ~R 14 each independently represents a hydrocarbon group which may have a substituent.
[0019] In the substituent (C), the bond at the left end represents the bond between the negative charge of the anionic group and the positive charge of the quaternary ammonium cation. Examples of anionic groups that can be negatively charged include "-SO 3 - " is an anionic group in which an active proton is bonded to an oxygen atom.
[0020] R in chemical formula (C) 11 ~R 14 R in chemical formula (C) is a hydrocarbon group which may have a substituent. 11 ~R 14 is a substituent derived from a quaternary ammonium compound. Examples of the hydrocarbon group in chemical formula (C) include an aliphatic hydrocarbon group having 1 to 20 carbon atoms which may have a substituent, and an aromatic hydrocarbon group having 6 to 20 carbon atoms which may have a substituent. Examples of the aliphatic hydrocarbon group include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, and an octyl group. Examples of the substituent on the aliphatic hydrocarbon group include a phenyl group and a hydroxyl group. Examples of the aromatic hydrocarbon group include a phenyl group and a naphthyl group. Examples of the substituent on the aromatic hydrocarbon group include an alkyl group having 1 to 5 carbon atoms and a hydroxyl group.
[0021] In order to improve dispersibility in organic solvents and conductivity, the quaternary ammonium compound preferably has a substituent on the nitrogen atom having 3 or more carbon atoms, more preferably has a substituent on the nitrogen atom having 5 or more carbon atoms, and even more preferably has a substituent on the nitrogen atom having 7 or more carbon atoms. The upper limit of the carbon number of each substituent on the nitrogen atom is not particularly limited, and taking into consideration solubility in solvents and reactivity, it is, for example, preferably 40 or less, more preferably 30 or less, and even more preferably 20 or less. In addition, the R 11 ~R 14 The total number of carbon atoms is preferably 8 to 44, more preferably 12 to 40, and further preferably 16 to 36. The number of carbon atoms in each of the substituents on the nitrogen atom may be the same or different.
[0022] The quaternary ammonium compound is preferably water-insoluble, where water-insoluble means that the solubility in 100 g of water at 20° C. is less than 1 g. The water-insoluble quaternary ammonium compound has high reactivity with polyanions in the reaction liquid described below, and therefore can easily form the desired substituent (C).
[0023] The quaternary ammonium compound is preferably a tetraalkylammonium halide, because it has high reactivity with polyanions, and the reaction product is difficult to dissolve in the aqueous dispersion medium and easily precipitates. As the halogen ion of the counter anion, a bromide ion or a chloride ion is preferable, and a bromide ion is more preferable.
[0024] Specific examples of quaternary ammonium compounds include quaternary ammonium salts such as tetramethylammonium salt, tetraethylammonium salt, tetrapropylammonium salt, tetrabutylammonium salt, tetra-n-octylammonium salt, tetraphenylammonium salt, tetrabenzylammonium salt, and tetranaphthylammonium salt. Examples of the counter anion of the ammonium cation include halogen ions such as bromide ion and chloride ion, and hydroxy ion.
[0025] The content of the polyanion in the conductive complex is preferably in the range of 1 part by mass to 1000 parts by mass, more preferably 10 parts by mass to 700 parts by mass, and even more preferably 100 parts by mass to 500 parts by mass, per 100 parts by mass of the π-conjugated conductive polymer. If the content of the polyanion is equal to or greater than the lower limit, the doping effect on the π-conjugated conductive polymer tends to be stronger, and the conductivity becomes higher. On the other hand, if the content of the polyanion is equal to or less than the upper limit, the amount of anion groups not involved in doping is appropriately suppressed, and the anion groups can be easily converted to hydrophobicity when reacting with a quaternary ammonium compound.
[0026] The content of the conductive complex relative to the total mass of the conductive polymer-containing liquid is, for example, preferably 0.01% by mass to 5% by mass, more preferably 0.1% by mass to 2% by mass, and even more preferably 0.2% by mass to 1% by mass. When the content is within the above preferred range, the dispersion stability of the conductive complex is further improved.
[0027] [Dispersion medium] The isopropyl alcohol contained in the conductive polymer-containing liquid of this embodiment is a dispersion medium that disperses the conductive complex that has been hydrophobized by reaction with the quaternary ammonium compound. The content of isopropyl alcohol relative to the total mass of the conductive polymer-containing liquid is 84% by mass or more, preferably 86% by mass or more, more preferably 88% by mass or more, even more preferably 90% by mass or more, and particularly preferably 92% by mass or more. The upper limit of the content of isopropyl alcohol is, for example, 99.9% by mass or less, leaving room for the inclusion of the conductive complex. When it is in the above preferred range, the dispersion stability of the conductive complex is improved, and the wettability to the substrate is also excellent.
[0028] The conductive polymer-containing liquid of this embodiment may contain a small amount of water. The water content of the conductive polymer-containing liquid is preferably 10% by mass or less, more preferably 5% by mass or less, further preferably 2% by mass or less, and particularly preferably 1% by mass or less, based on the total mass of the conductive polymer-containing liquid. When the water content is low, the dispersion stability of the conductive composite is improved, and the wettability to the substrate is also excellent.
[0029] The conductive polymer-containing liquid of this embodiment may contain an organic solvent other than isopropyl alcohol. Examples of the organic solvent include hydrocarbon solvents, ketone solvents, alcohol solvents, ether solvents, and nitrogen atom-containing compound solvents. Examples of the hydrocarbon solvent include aliphatic hydrocarbon solvents and aromatic hydrocarbon solvents. Examples of the aliphatic hydrocarbon solvent include pentane, hexane, heptane, octane, decane, cyclohexane, methylcyclohexane, etc. Examples of the aromatic hydrocarbon solvent include benzene, toluene, xylene, ethylbenzene, propylbenzene, isopropylbenzene, etc. Examples of the ketone solvent include diethyl ketone, methyl propyl ketone, methyl butyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, methyl amyl ketone, diisopropyl ketone, methyl ethyl ketone, acetone, and diacetone alcohol. Examples of the alcohol solvent include methanol, ethanol, 1-propanol, n-butanol, t-butanol, and allyl alcohol. Examples of the ether solvent include diethyl ether, dimethyl ether, and propylene glycol dialkyl ether. Examples of the nitrogen atom-containing compound solvent include N-methylpyrrolidone, dimethylacetamide, and dimethylformamide. Among the above, alcohol-based solvents having high compatibility with isopropyl alcohol are preferred, and ethanol or 1-propanol are more preferred.
[0030] (Highly conductive agent) The conductive polymer-containing liquid of this embodiment may contain a conductivity enhancing agent. Here, the above-mentioned π-conjugated conductive polymers, polyanions, organic solvents, and quaternary ammonium compounds are not classified as high-conductivity agents. The conductive agent is preferably at least one compound selected from the group consisting of saccharides, nitrogen-containing aromatic cyclic compounds, compounds having two or more hydroxyl groups, compounds having one or more hydroxyl groups and one or more carboxyl groups, compounds having an amide group, compounds having an imide group, lactam compounds, compounds having a glycidyl group, and compounds having at least one unsaturated bond and at least one hydroxyl group and having 3 to 5 carbon atoms. Among them, compounds having at least one unsaturated bond and at least one hydroxyl group and having 3 to 5 carbon atoms are more preferable because they have good solubility in isopropyl alcohol and can easily achieve the effect of increasing conductivity. Here, the unsaturated bond is not limited to an unsaturated bond between adjacent carbon atoms, but also includes an unsaturated bond between adjacent atoms other than carbon atoms. The conductive polymer-containing liquid of this embodiment may contain one type of highly conductive agent, or two or more types of highly conductive agents.
[0031] Specific examples of suitable conductive agents include at least one selected from propylene glycol, dimethyl sulfoxide, hydroxyethyl acrylamide, N,N-dimethyl acrylamide, 2,3-butenediol, and 2,3-butynediol.
[0032] The content of the conductive agent in the conductive polymer-containing liquid is preferably from 1 to 15% by mass, more preferably from 2 to 10% by mass, and even more preferably from 3 to 7% by mass. When the content is equal to or greater than the lower limit of the above range, the effect of improving the conductivity due to the addition of the conductivity enhancing agent is sufficiently exhibited, and when the content is equal to or less than the upper limit of the above range, the dispersion stability of the conductive composite is further improved.
[0033] (Other additives) The conductive polymer-containing liquid of this embodiment may contain other known additives. The additives are not particularly limited as long as the effects of the present invention can be obtained. For example, surfactants, inorganic conductive agents, antifoaming agents, coupling agents, antioxidants, ultraviolet absorbing agents, etc. can be used. The surfactant may be a nonionic, anionic or cationic surfactant, with the nonionic surfactant being preferred from the standpoint of storage stability. A polymer surfactant such as polyvinylpyrrolidone may also be added. Examples of the inorganic conductive agent include metal ions, conductive carbon, etc. Metal ions can be generated by dissolving a metal salt in water. The antifoaming agent includes silicone resin, polydimethylsiloxane, silicone oil, and the like. The coupling agent may be a silane coupling agent having a vinyl group or an amino group. Examples of the antioxidant include phenol-based antioxidants, amine-based antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, and sugars. Examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, salicylate-based ultraviolet absorbers, cyanoacrylate-based ultraviolet absorbers, oxanilide-based ultraviolet absorbers, hindered amine-based ultraviolet absorbers, and benzoate-based ultraviolet absorbers. When the conductive polymer-containing liquid of this embodiment contains the above-mentioned additive, the content ratio thereof is appropriately determined depending on the type of additive, but can be, for example, in the range of 0.001 parts by mass or more and 5 parts by mass or less per 100 parts by mass of the conductive composite.
[0034] <Particle size> The dispersion stability of the conductive polymer-containing liquid of this embodiment can be evaluated by the particle size of the conductive complex in the liquid. Comparing the particle size Q0 immediately after production and the particle size Q1 after storage, the closer the ratio Q1 / Q0 is to 1, the better the dispersion stability is. The conductive complex particles gradually aggregate after production, and when they aggregate to a degree that can be seen with the naked eye, they settle and form a precipitate. A conductive polymer-containing liquid containing such aggregated conductive complex is difficult to coat, and even if it can be coated, the distribution of the conductive complex contained in the coating film becomes uneven, resulting in poor conductivity of the conductive layer made of the coating film.
[0035] The particle size of the conductive complex contained in the conductive polymer-containing liquid of this embodiment, when the concentration of the conductive complex relative to the total mass of the conductive polymer-containing liquid is adjusted to 0.1 to 0.5 mass %, is preferably 10 nm to 500 nm, more preferably 50 nm to 450 nm, and even more preferably 100 nm to 400 nm at 25° C. Within these preferred ranges, the dispersion stability of the conductive complex is further improved. The particle size is determined as a cumulant average particle size measured by dynamic light scattering.
[0036] <Method for producing conductive polymer-containing liquid> A second aspect of the present invention is a method for producing a conductive polymer-containing liquid, comprising: a reaction precipitation step of adding a conductive polymer aqueous dispersion containing a conductive complex containing a π-conjugated conductive polymer and a polyanion to an organic solution (reaction liquid) containing a quaternary ammonium compound, thereby reacting a part of anion groups of the polyanion with the quaternary ammonium compound and precipitating a reaction product; a recovery step of recovering the reaction product; and a preparation step of dispersing the recovered reaction product in an organic solvent containing isopropyl alcohol to obtain a conductive polymer-containing liquid, wherein the content of the isopropyl alcohol with respect to the total mass of the conductive polymer-containing liquid is 84 mass% or more. According to the production method of this embodiment, the conductive polymer-containing liquid of the first embodiment can be produced.
[0037] The manufacturing method of this embodiment may further include a washing step between the recovery step and the preparation step. In addition, a conductivity enhancing agent or the like may be further added in the preparation step.
[0038] [Reaction precipitation process] This process is a process in which a conductive polymer aqueous dispersion is added to an organic solution (reaction liquid) containing a quaternary ammonium compound, thereby precipitating a reaction product between the conductive complex and the quaternary ammonium compound in the reaction liquid.
[0039] When the conductive polymer aqueous dispersion is added to the reaction solution, the quaternary ammonium compound reacts stably with some of the anion groups of the polyanion of the conductive complex, forming the aforementioned substituent (C) and making the conductive complex hydrophobic, improving the dispersion stability against isopropyl alcohol, making it difficult to stably disperse in the reaction solution, and causing precipitation to form a precipitate.
[0040] The organic solvent contained in the reaction liquid may be one type or two or more types. As the organic solvent, the organic solvents already exemplified can be used, and examples thereof include methanol, ethanol, 1-propanol, isopropyl alcohol, n-butanol, t-butanol, and allyl alcohol.
[0041] The content of the quaternary ammonium compound in the reaction liquid is preferably 10 parts by mass or more and 5,000 parts by mass or less, more preferably 100 parts by mass or more and 1,000 parts by mass or less, and even more preferably 150 parts by mass or more and 500 parts by mass or less, relative to 100 parts by mass of the total mass of the conductive complex added. When the content is at least the lower limit of the above range, the reaction efficiency between the conductive complex and the quaternary ammonium compound is increased, and the reaction product can be easily obtained. When the content is equal to or less than the upper limit of the above range, a decrease in the conductivity of the conductive composite due to contamination with unreacted quaternary ammonium compound can be prevented.
[0042] The conductive polymer aqueous dispersion is a dispersion in which a conductive complex containing a π-conjugated conductive polymer and a polyanion is contained in an aqueous dispersion medium. Here, the aqueous dispersion medium is water or a mixture of water and a water-soluble organic solvent. The water-soluble organic solvent is one that dissolves in an amount of 1 g or more per 100 g of water (20° C.). Examples of the water-soluble organic solvent include alcohol-based solvents, ketone-based solvents, and ester-based solvents. The aqueous dispersion medium may contain one type of water-soluble organic solvent, or two or more types of water-soluble organic solvents. The content of water relative to the total mass of the aqueous dispersion medium is preferably more than 50% by mass, more preferably 60% by mass or more, even more preferably 80% by mass or more, and may be 100% by mass. When the content of water is large, the dispersibility of the conductive composite is increased, and the reaction efficiency with the quaternary ammonium compound is increased. Furthermore, the reaction product is easily precipitated in the reaction liquid.
[0043] The conductive polymer aqueous dispersion can be obtained, for example, by chemically oxidizing a monomer that forms a π-conjugated conductive polymer in an aqueous solution of a polyanion. Alternatively, a commercially available conductive polymer aqueous dispersion can be used. A known catalyst may be used in the chemical oxidative polymerization. For example, a catalyst and an oxidizing agent may be used. Examples of the catalyst include transition metal compounds such as ferric chloride, ferric sulfate, ferric nitrate, and cupric chloride. Examples of the oxidizing agent include persulfates such as ammonium persulfate, sodium persulfate, and potassium persulfate.
[0044] The content of the π-conjugated conductive polymer and the polyanion relative to the total mass of the aqueous conductive polymer dispersion is preferably from 0.1% by mass to 5% by mass, more preferably from 0.5% by mass to 2% by mass, and even more preferably from 0.8% by mass to 1.5% by mass. When the content is within the above preferred range, the dispersibility of the conductive complex is improved, and the reaction efficiency with the quaternary ammonium compound is increased.
[0045] The volume ratio (V1 / V2) of the volume V2 of the conductive polymer aqueous dispersion to be added to the volume V1 of the reaction liquid is preferably from 0.3 to 3.0, more preferably from 0.5 to 2.5, and even more preferably from 0.8 to 2.0. When the temperature is within the above preferred range, the reaction proceeds stably and the reaction product precipitates easily.
[0046] The method of adding the conductive polymer aqueous dispersion to the reaction liquid is not particularly limited, and a desired amount may be added all at once in a few seconds, or may be added slowly dropwise. From the viewpoint of obtaining a conductive composite having a small particle size and increasing the conductivity, the method of adding slowly dropwise is preferred. The rate at which the conductive polymer aqueous dispersion is dropped into the reaction liquid is preferably 1 minute to 3 hours, more preferably 10 minutes to 2 hours, from the start to the end of the drop, assuming that a constant amount is continuously dropped. During the drop, it is preferable to gently stir the reaction liquid. When the temperature is within the above preferred range, the reaction proceeds stably and the reaction product precipitates easily.
[0047] The amount of the conductive polymer aqueous dispersion added dropwise to the reaction liquid is preferably 0.1 to 100 ml / min, and more preferably 1 to 10 ml / min. During the dropwise addition, it is preferable to gently stir the reaction liquid. When the temperature is within the above preferred range, the reaction proceeds stably and the reaction product precipitates easily.
[0048] When the conductive polymer dispersion is added to the reaction liquid and gently stirred, a reaction product precipitates within a few minutes to a few hours. The completion of the reaction can be confirmed by visually observing the completion of the precipitation of the reaction product.
[0049] The temperature of the reaction solution is not particularly limited and may be, for example, 5 to 40°C.
[0050] [Recovery process] This step is a step of recovering the reaction product as a precipitate. The recovery method is not particularly limited, and recovery can be performed, for example, by decantation or filtration. It is preferable that the water content of the recovered reaction product (precipitate) is as small as possible, and it is most preferable that it contains no water at all, but from a practical standpoint, it may contain water in the range of 10 mass % or less. Methods for reducing the moisture content include, for example, washing off the precipitate with an organic solvent, drying the precipitate, and the like.
[0051] [Cleaning process] It is preferable to add a washing step between the recovery step and the preparation step. The washing step is a step of washing the precipitate with an organic solvent for washing. This washing step can remove remaining water, unreacted quaternary ammonium compounds, impurities contained in the conductive polymer aqueous dispersion, and the like.
[0052] The cleaning organic solvent is preferably one that can clean the precipitate while minimizing dissolution of the precipitate. For this reason, the cleaning organic solvent is preferably an alcohol-based solvent other than isopropyl alcohol. The cleaning organic solvent may contain one type of organic solvent or two or more types of organic solvents. The washing method is not particularly limited, and for example, the precipitate may be washed by pouring an organic washing solvent over the precipitate, or the precipitate may be washed by stirring in the organic washing solvent.
[0053] [Preparation process] This step is a step of adding an organic solvent containing isopropyl alcohol to the precipitate to obtain a conductive polymer-containing liquid.
[0054] As the organic solvent in this step, the organic solvent contained in the conductive polymer-containing liquid of the first embodiment can be used. Since the conductive complex is modified with a quaternary ammonium compound, isopropyl alcohol is used to thoroughly disperse the conductive complex. In addition to isopropyl alcohol, an optional organic solvent, for example, one or more selected from alcohol-based solvents other than isopropyl alcohol, may be added. The content of each solvent contained in the organic solvent is preferably within the preferred range exemplified in the first embodiment.
[0055] The conductive polymer-containing liquid obtained by adding an organic solvent to the precipitate may be stirred and dispersed. The stirring method is not particularly limited, and may be a weak shear stirring such as with a stirrer, or may be a high shear stirring using a dispersing machine (homogenizer, etc.).
[0056] The content of the conductive complex relative to the total mass of the conductive polymer-containing liquid dispersed by the high-pressure homogenizer is, for example, preferably from 0.01% by mass to 5% by mass, more preferably from 0.05% by mass to 2% by mass, and even more preferably from 0.1% by mass to 1% by mass. When the concentration is within the above range, the dispersibility of the conductive composite can be sufficiently increased.
[0057] (Addition of high conductivity agents and other additives) The conductive polymer-containing liquid may contain the conductive agent and other additives.
[0058] <Conductive laminate> A third aspect of the present invention is a conductive laminate comprising a substrate and a conductive layer formed on at least one surface of the substrate, the conductive layer being made of a cured product of the conductive polymer-containing liquid of the first aspect.
[0059] [Conductive layer] The average thickness of the conductive layer provided on at least one surface of the substrate is, for example, preferably 10 nm to 100 μm, more preferably 20 nm to 50 μm, and even more preferably 30 nm to 30 μm. When the average thickness of the conductive layer is equal to or greater than the lower limit, high conductivity can be exhibited, and when the average thickness is equal to or less than the upper limit, the adhesion of the conductive layer to the substrate is further improved.
[0060] The conductive layer included in the conductive laminate of this embodiment contains a conductive complex containing a π-conjugated conductive polymer and a polyanion. When the conductive polymer-containing liquid applied to the substrate contains a binder component, the conductive layer contains the binder component or a cured product of the binder component.
[0061] [Base material] The substrate constituting the conductive laminate of this embodiment may be a substrate made of an insulating material or a substrate made of a conductive material. The shape of the substrate is not particularly limited, and examples thereof include a shape mainly having a flat surface such as a film or a substrate. Examples of insulating materials include glass, synthetic resin, and ceramics. The conductive material may be a metal, a conductive metal oxide, carbon, or the like.
[0062] (Film substrate) When a film substrate is used as the substrate, the conductive laminate becomes a conductive film. The film substrate may be, for example, a plastic film made of a synthetic resin, such as ethylene-methyl methacrylate copolymer resin, ethylene-vinyl acetate copolymer resin, polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinyl alcohol, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyacrylate, polycarbonate, polyvinylidene fluoride, polyarylate, styrene-based elastomer, polyester-based elastomer, polyethersulfone, polyetherimide, polyetheretherketone, polyphenylene sulfide, polyimide, cellulose triacetate, cellulose acetate propionate, etc. From the viewpoint of improving the adhesion between the film substrate and the conductive layer, the synthetic resin for the film substrate is preferably the same type of resin as the binder resin, and among these, a polyester resin such as polyethylene terephthalate is preferred.
[0063] The synthetic resin for the film substrate may be either amorphous or crystalline. The film substrate may be either unstretched or stretched. The film substrate may be subjected to a surface treatment such as a corona discharge treatment, a plasma treatment, or a flame treatment in order to further improve the adhesiveness of the conductive layer formed from the conductive polymer-containing liquid.
[0064] The average thickness of the film substrate is preferably 5 μm to 500 μm, more preferably 20 μm to 200 μm. If the average thickness of the film substrate is equal to or more than the lower limit, the film is less likely to break, and if the average thickness is equal to or less than the upper limit, the film can have sufficient flexibility. The average thickness of the film substrate is calculated by measuring the thickness at 10 randomly selected points and averaging the measured values.
[0065] (Glass substrate) Examples of the glass substrate include an alkali-free glass substrate, a soda-lime glass substrate, a borosilicate glass substrate, and a quartz glass substrate. If the substrate contains an alkali component, the conductivity of the conductive layer tends to decrease, so among the above glass substrates, an alkali-free glass is preferred. Here, the alkali-free glass refers to a glass composition in which the content of the alkali component is 0.1 mass% or less with respect to the total mass of the glass composition.
[0066] The average thickness of the glass substrate is preferably 100 μm or more and 3000 μm or less, and more preferably 100 μm or more and 1000 μm or less. If the average thickness of the glass substrate is equal to or more than the lower limit, the substrate is less likely to be broken, and if the average thickness is equal to or less than the upper limit, the substrate can contribute to making the conductive laminate thinner. The average thickness of the glass substrate is calculated by measuring the thickness at 10 randomly selected points and averaging the measured values.
[0067] <Method for manufacturing conductive laminate> A fourth aspect of the present invention is a method for producing a conductive laminate, the method including applying the conductive polymer-containing liquid of the first aspect to at least one surface of a substrate. The conductive laminate of the third aspect can be produced by the production method of this aspect.
[0068] Examples of a method for applying (coating) the conductive polymer-containing liquid of the first embodiment to an arbitrary surface of a substrate include a method using a coater such as a gravure coater, a roll coater, a curtain flow coater, a spin coater, a bar coater, a reverse coater, a kiss coater, a fountain coater, a rod coater, an air doctor coater, a knife coater, a blade coater, a cast coater, or a screen coater; a method using a sprayer such as an air spray, an airless spray, or a rotor dampening; and an immersion method such as dipping.
[0069] The amount of conductive polymer-containing liquid applied to the substrate is not particularly limited, but taking into consideration uniform and even application, conductivity, and film strength, a solid content of 0.01 g / m 2 More than 10.0g / m 2 The following ranges are preferred:
[0070] The coating film made of the conductive polymer-containing liquid applied onto the substrate is dried to remove the dispersion medium, thereby obtaining a conductive laminate in which a conductive layer (conductive film) is formed by hardening the coating film. Methods for drying the coating film include heat drying, vacuum drying, etc. Examples of heat drying that can be used include hot air heating and infrared heating. When applying heat drying, the heating temperature is appropriately set depending on the dispersion medium used, but is usually within the range of 50° C. to 150° C. Here, the heating temperature is the set temperature of the drying device. A suitable drying time within the above heating temperature range is preferably 1 minute to 30 minutes, more preferably 5 minutes to 15 minutes.
[0071] In the case where the conductive polymer-containing liquid contains an active energy ray-curable binder component, the method may further include an active energy ray irradiation step of irradiating the dried conductive polymer coating film with active energy rays after the drying step. By including the active energy ray irradiation step, the rate of forming the conductive layer can be increased, and the productivity of the conductive film can be improved. In the case where the active energy ray irradiation step is included, examples of the active energy ray used include ultraviolet rays, electron beams, visible light, etc. Examples of the light source of the ultraviolet ray that can be used include light sources such as ultra-high pressure mercury lamps, high pressure mercury lamps, low pressure mercury lamps, carbon arcs, xenon arcs, and metal halide lamps. EXAMPLES
[0072] (Production Example 1) Production of polystyrene sulfonic acid 206 g of sodium styrenesulfonate was dissolved in 1000 ml of ion-exchanged water, and while stirring at 80° C., 1.14 g of an oxidizing agent solution of ammonium persulfate previously dissolved in 10 ml of water was added dropwise over 20 minutes, and the solution was stirred for 12 hours. 1000ml of sulfuric acid diluted to 10% by mass was added to the obtained sodium styrene sulfonate-containing solution, and about 1000ml of the solvent was removed from the polystyrene sulfonic acid-containing solution by ultrafiltration. Next, 2000ml of ion-exchanged water was added to the remaining liquid, and about 2000ml of the solvent was removed by ultrafiltration, and the polystyrene sulfonic acid was washed with water. This washing operation was repeated three times. Water in the resulting solution was removed under reduced pressure to obtain colorless solid polystyrene sulfonic acid.
[0073] (Production Example 2) Synthesis of a conductive polymer dispersion containing a π-conjugated conductive polymer and a polyanion 14.2 g of 3,4-ethylenedioxythiophene and a solution in which 36.7 g of polystyrene sulfonic acid was dissolved in 2000 ml of ion-exchanged water were mixed at 20°C. The resulting mixed solution was kept at 20° C., and while stirring, 29.64 g of ammonium persulfate and 8.0 g of an oxidation catalyst solution of ferric sulfate dissolved in 200 ml of ion-exchanged water were slowly added, followed by stirring for 3 hours to allow the reaction to proceed. To the reaction solution obtained, 2000 ml of ion-exchanged water was added, and about 2000 ml of the solvent was removed by ultrafiltration. This operation was repeated three times. Next, 200 ml of sulfuric acid diluted to 10% by mass and 2000 ml of ion-exchanged water were added to the obtained solution, and about 2000 ml of the solvent was removed by ultrafiltration. 2000 ml of ion-exchanged water was added to the remaining liquid, and about 2000 ml of the solution was removed by ultrafiltration. This operation was repeated three times. Furthermore, 2000 ml of ion-exchanged water was added to the obtained solution, and about 2000 ml of the solvent was removed by ultrafiltration. This operation was repeated five times to obtain a polystyrene sulfonate-doped poly(3,4-ethylenedioxythiophene) (PEDOT-PSS) aqueous dispersion with a concentration of 1.2 mass%. The PSS content in the PEDOT-PSS was 75 mass%.
[0074] (Production Example 3) Reaction with quaternary ammonium salt A 100g of the PEDOT-PSS aqueous dispersion prepared in Production Example 2 was added dropwise to the organic layer (organic solution) prepared by dissolving 2.9g of tetrabutylammonium bromide in 100g of ethanol, and the mixture was stirred for 30 minutes. As a result, a reaction product of tetrabutylammonium bromide and a conductive complex was precipitated. This precipitate was collected by filtration, 100g of isopropyl alcohol was added, and the precipitate was lightly suspended while stirring for 30 minutes, and then the precipitate was collected by filtration again. This washing operation was repeated once more. As a result, 1.1g of a conductive complex having the aforementioned substituent (C) was obtained.
[0075] (Production Example 4) Reaction with quaternary ammonium salt B 100g of the PEDOT-PSS aqueous dispersion prepared in Production Example 2 was added dropwise to the organic layer in which 2.4g of tetraoctylammonium bromide was dissolved in 200g of ethanol, and the mixture was stirred for 30 minutes. As a result, a reaction product of tetraoctylammonium bromide and a conductive complex was precipitated. This precipitate was filtered and washed in the same manner as in Production Example 3, to obtain 1.1g of a conductive complex having the aforementioned substituent (C).
[0076] (Production Example 5) Reaction with amine compounds 100g of the PEDOT-PSS aqueous dispersion prepared in Production Example 2 was added dropwise to an organic layer prepared by dissolving 5g of trioctylamine in 200g of ethanol, and the mixture was stirred for 30 minutes. As a result, a reaction product of trioctylamine and a conductive complex was precipitated. This precipitate was filtered and washed in the same manner as in Production Example 3, yielding 1.1g of a conductive complex that had reacted with trioctylamine.
[0077] Example 1 1.1 g of the conductive complex obtained in Production Example 3 and 274 g of isopropyl alcohol were added and treated with a high-pressure homogenizer to obtain an initial conductive polymer-containing liquid. The particle size (cumulant average particle size) Q0 of the conductive complex contained in this conductive polymer-containing liquid was measured by dynamic light scattering, and the results are shown in Table 1. Next, the conductive polymer-containing liquid was applied to a PET film (Lumirror T60, manufactured by Toray Industries, Inc.) using a bar coater #8, and dried at 120°C for 2 minutes to obtain a conductive film. The surface resistivity R0 of this conductive film was measured, and the results are shown in Table 1. Next, this conductive film was left to stand for 4 days in an environment at 80° C. The surface resistivity R1 of the conductive film after this heat treatment was measured, and the results are shown in Table 1. Furthermore, the initial conductive polymer-containing liquid was left to stand for 10 days at 40° C. to obtain a conductive polymer-containing liquid, and the particle size (cumulant average particle size) Q1 of the conductive complex contained therein was measured by dynamic light scattering, and the results are shown in Table 1.
[0078] Example 2 5 g of propylene glycol (PG) was mixed with 95 g of the initial conductive polymer-containing liquid obtained in Example 1. Except for using this as the initial conductive polymer-containing liquid, the conductive polymer-containing liquid after storage was obtained in the same manner as in Example 1, and the particle size Q0 and particle size Q1 were measured, and a conductive film was produced and the surface resistivities R0 and R1 were measured. The results are shown in Table 1.
[0079] Example 3 Except for changing 5 g of propylene glycol to 5 g of dimethyl sulfoxide (DMSO), the same procedure as in Example 2 was followed to obtain each conductive polymer-containing liquid, measure the particle size Q0 and particle size Q1, and prepare a conductive film to measure the surface resistivity R0 and R1. The results are shown in Table 1.
[0080] Example 4 Except for changing 5 g of propylene glycol to 5 g of 2-hydroxyacrylamide (HEAA), the same procedure as in Example 2 was followed to obtain each conductive polymer-containing liquid, measure the particle size Q0 and particle size Q1, and prepare a conductive film to measure the surface resistivity R0 and R1. The results are shown in Table 1.
[0081] Example 5 Except for changing 5 g of propylene glycol to 5 g of N,N-dimethylacrylamide (DMAA), the same procedure as in Example 2 was followed to obtain each conductive polymer-containing liquid, measure the particle size Q0 and particle size Q1, and prepare a conductive film to measure the surface resistivity R0 and R1. The results are shown in Table 1.
[0082] Example 6 Except for changing 5 g of propylene glycol to 5 g of 2,3-butenediol, the same procedure as in Example 2 was followed to obtain each conductive polymer-containing liquid, measure the particle size Q0 and particle size Q1, and prepare a conductive film to measure the surface resistivity R0 and R1. The results are shown in Table 1.
[0083] Example 7 Except for changing 5 g of propylene glycol to 5 g of 2,3-butynediol, the same procedure as in Example 2 was followed to obtain each conductive polymer-containing liquid, measure the particle size Q0 and particle size Q1, and prepare a conductive film to measure the surface resistivity R0 and R1. The results are shown in Table 1.
[0084] Example 8 Except for changing 274 g of isopropyl alcohol to 248 g of isopropyl alcohol and 26 g of ethanol, the same procedure as in Example 1 was followed to obtain each conductive polymer-containing liquid, measure the particle size Q0 and particle size Q1, and prepare a conductive film to measure the surface resistivity R0 and R1. The results are shown in Table 1.
[0085] Example 9 Except for changing 274 g of isopropyl alcohol to 248 g of isopropyl alcohol and 26 g of 1-propanol, the same procedure as in Example 1 was followed to obtain each conductive polymer-containing liquid, measure the particle size Q0 and particle size Q1, and prepare a conductive film to measure the surface resistivity R0 and R1. The results are shown in Table 1.
[0086] Example 10 Each conductive polymer-containing liquid was obtained, the particle size Q0 and particle size Q1 were measured, and a conductive film was produced and the surface resistivities R0 and R1 were measured in the same manner as in Example 1, except that the conductive composite 1.1 g obtained in Production Example 3 was replaced with the conductive composite 1.1 g obtained in Production Example 4. The results are shown in Table 1.
[0087] Example 11 95 g of the initial conductive polymer-containing liquid obtained in Example 10 was mixed with 5 g of propylene glycol. Except for using this as the initial conductive polymer-containing liquid, the conductive polymer-containing liquid after storage was obtained in the same manner as in Example 1, and the particle size Q0 and particle size Q1 were measured, and a conductive film was produced and the surface resistivities R0 and R1 were measured. The results are shown in Table 1.
[0088] Example 12 Except for changing 5 g of propylene glycol to 5 g of dimethyl sulfoxide, the same procedure as in Example 11 was followed to obtain each conductive polymer-containing liquid, measure the particle size Q0 and particle size Q1, prepare a conductive film, and measure the surface resistivity R0 and R1. The results are shown in Table 1.
[0089] (Example 13) Except for changing 5 g of propylene glycol to 5 g of 2-hydroxyacrylamide, the same procedure as in Example 11 was followed to obtain each conductive polymer-containing liquid, measure the particle size Q0 and particle size Q1, and prepare a conductive film to measure the surface resistivity R0 and R1. The results are shown in Table 2.
[0090] Example 14 Except for changing 5 g of propylene glycol to 5 g of N,N-dimethylacrylamide, the same procedure as in Example 11 was followed to obtain each conductive polymer-containing liquid, measure the particle size Q0 and particle size Q1, and prepare a conductive film to measure the surface resistivity R0 and R1. The results are shown in Table 2.
[0091] Example 15 Except for changing 5 g of propylene glycol to 5 g of 2,3-butenediol, the same procedure as in Example 11 was followed to obtain each conductive polymer-containing liquid, measure the particle size Q0 and particle size Q1, and prepare a conductive film to measure the surface resistivity R0 and R1. The results are shown in Table 2.
[0092] Example 16 Except for changing 5 g of propylene glycol to 5 g of 2,3-butynediol, the same procedure as in Example 11 was followed to obtain each conductive polymer-containing liquid, measure the particle size Q0 and particle size Q1, and prepare a conductive film to measure the surface resistivity R0 and R1. The results are shown in Table 2.
[0093] (Example 17) Except for changing 274 g of isopropyl alcohol to 248 g of isopropyl alcohol and 26 g of ethanol, the same procedure as in Example 10 was followed to obtain each conductive polymer-containing liquid, measure the particle size Q0 and particle size Q1, and prepare a conductive film to measure the surface resistivity R0 and R1. The results are shown in Table 2.
[0094] (Example 18) Except for changing 274 g of isopropyl alcohol to 248 g of isopropyl alcohol and 26 g of 1-propanol, the same procedure as in Example 10 was followed to obtain each conductive polymer-containing liquid, measure the particle size Q0 and particle size Q1, and prepare a conductive film to measure the surface resistivity R0 and R1. The results are shown in Table 2.
[0095] Comparative Example 1 Each conductive polymer-containing liquid was obtained, the particle size Q0 and particle size Q1 were measured, and a conductive film was produced and the surface resistivities R0 and R1 were measured in the same manner as in Example 1, except that the conductive composite 1.1 g obtained in Production Example 3 was replaced with the conductive composite 1.1 g obtained in Production Example 5. The results are shown in Table 2.
[0096] Comparative Example 2 Except for changing 274 g of isopropyl alcohol to 274 g of ethanol, the same procedure as in Example 1 was followed to obtain each conductive polymer-containing liquid, measure the particle size Q0 and particle size Q1, prepare a conductive film, and measure the surface resistivity R0 and R1. The results are shown in Table 2.
[0097] Comparative Example 3 Except for changing 274 g of isopropyl alcohol to 220 g of isopropyl alcohol and 54 g of ethanol, the same procedure as in Example 1 was followed to obtain each conductive polymer-containing liquid, measure the particle size Q0 and particle size Q1, and prepare a conductive film to measure the surface resistivity R0 and R1. The results are shown in Table 2.
[0098] Comparative Example 4 Except for changing 274 g of isopropyl alcohol to 220 g of isopropyl alcohol and 54 g of ethanol, the same procedure as in Example 10 was followed to obtain each conductive polymer-containing liquid, measure the particle size Q0 and particle size Q1, and prepare a conductive film to measure the surface resistivity R0 and R1. The results are shown in Table 2.
[0099] Comparative Example 5 An organic layer (organic solution) prepared by dissolving 2.9 g of tetrabutylammonium bromide in 100 g of ethanol was added dropwise to 100 g of the PEDOT-PSS aqueous dispersion prepared in Production Example 2, but tetrabutylammonium bromide precipitated and the reaction was insufficient, so no conductive composite precipitate was obtained.
[0100] [Method of measuring particle size] The conductive polymer-containing liquid prepared in each example was used as a sample (25°C) and a zeta potential / particle size / molecular weight measurement system (ELSZ-2000ZS, Otsuka Electronics Co., Ltd.) was used to determine the particle size by dynamic light scattering. The average particle diameter d (hydrodynamic diameter) and polydispersity index were determined from the autocorrelation function obtained by the photon correlation method using the cumulant method.
[0101] [Surface resistivity measurement] For the conductive films produced in each example, the surface resistivity of the conductive layer was measured using a resistivity meter (Hiresta manufactured by Nitto Seiko Analytech Co., Ltd.) under the condition of an applied voltage of 10V.
[0102] [Table 1]
[0103] [Table 2]
[0104] In the conductive polymer-containing liquid of each embodiment of the present invention, the conductive complex was reacted with a quaternary ammonium compound, so that the conductive complex was sufficiently dispersed in a dispersion medium containing isopropanol, and the dispersion stability was excellent. As a result, the particle size of the conductive complex was suppressed from increasing during standing. In addition, the conductive layer of the conductive film was good even after heating, and the heat resistance of the conductive layer was improved. In Comparative Example 1, the conductive composite was reacted with a tertiary amine, and therefore the dispersion stability in isopropyl alcohol was poor. In addition, the initial conductivity was also poor, and the heat resistance was also poor. In Comparative Example 2, the conductive composite was dispersed in ethanol, and therefore the dispersion stability was poor, and the initial conductivity was also poor. In Comparative Examples 3 and 4, the conductive composite had poor dispersion stability due to a low concentration of isopropyl alcohol in the dispersion medium, and also had poor initial electrical conductivity and poor heat resistance. In Comparative Example 5, an alcohol solution containing a quaternary ammonium compound was added dropwise to the aqueous dispersion of a conductive polymer, so that the quaternary ammonium compound could not be reacted sufficiently with the conductive complex.
Claims
1. A conductive polymer-containing liquid containing a conductive complex including a π-conjugated conductive polymer and a polyanion, and isopropyl alcohol, the polyanion is modified by reacting a portion of an anionic group of the polyanion with a quaternary ammonium compound; The content of the isopropyl alcohol relative to the total mass of the conductive polymer-containing liquid is 84 mass% or more, the π-conjugated conductive polymer contains poly(3,4-ethylenedioxythiophene); the polyanion comprises polystyrene sulfonic acid; the quaternary ammonium compound comprises a tetraalkylammonium halide; The conductive polymer-containing liquid, wherein the four alkyl groups of the tetraalkylammonium halide are a butyl group, a pentyl group, a hexyl group, a heptyl group or an octyl group.
2. The conductive polymer-containing liquid according to claim 1 , wherein the tetraalkylammonium halide includes at least one of tetrabutylammonium halide and tetraoctylammonium halide.
3. The conductive polymer-containing liquid according to claim 1 or 2, further comprising a conductivity enhancing agent.
4. 4. The conductive polymer-containing liquid according to claim 3, wherein the conductive agent contains a compound having one or more unsaturated bonds or one or more hydroxyl groups and having 3 to 5 carbon atoms.
5. The conductive polymer-containing liquid according to claim 3, wherein the highly conductive agent contains at least one selected from the group consisting of propylene glycol, dimethyl sulfoxide, hydroxyethyl acrylamide, N,N-dimethyl acrylamide, 2,3-butenediol, and 2,3-butynediol.
6. A conductive laminate comprising a substrate and a conductive layer formed on at least a portion of the substrate, the conductive layer being made of a cured product of the conductive polymer-containing liquid according to any one of claims 1 to 5.
7. A method for producing a conductive laminate, comprising applying the conductive polymer-containing liquid according to any one of claims 1 to 5 to at least a part of a substrate.
Citation Information
Patent Citations
Electroconductive layered product and method of manufacturing the same
JP2008147035A
Composition for an antistatic release agent and antistatic release film
JP2014189597A
Electroconductive polymer aqueous dispersion, manufacturing method of electroconductive polymer composite, manufacturing method of electroconductive polymer-containing liquid, manufacturing method of conductive film, and conductive film
JP2020097681A
Conductive polymer dispersion and method for producing the same, and conductive film and method for producing the same
JP2021095459A
Conductive polymer-containing liquid and method for producing the same, and conductive laminate and method for producing the same
JP2022075086A